2017
DOI: 10.5005/jp-journals-10051-0134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea and Black Tea on Mineralization of Artificially Demineralized Human Enamel in Comparison with 0.05% Sodium Fluoride: An in vitro Study

Abstract: Introduction:The newer preventive approach to caries has resulted in the increased use of remineralizing agents. The remineralizing ability of green tea and black tea is under research. Materials and methods:Two hundred premolar teeth were collected and a buccal window was exposed on the tooth sample by coating the rest of the teeth with nail varnish. The samples were artificially demineralized using Featherstone pH cycling technique. The test solutions of green tea and black tea were prepared by dissolving 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…Within-group comparison showed a significant increase in the microhardness values as compared to the demineralization phase. Several studies were in agreement with the result of the present study as they reported the remineralizing effect of black and green tea using different methods of assessment (4,(29)(30)(31) . This effect could be due to the availability of fluoride content in the black and green tea infusions.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Within-group comparison showed a significant increase in the microhardness values as compared to the demineralization phase. Several studies were in agreement with the result of the present study as they reported the remineralizing effect of black and green tea using different methods of assessment (4,(29)(30)(31) . This effect could be due to the availability of fluoride content in the black and green tea infusions.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in their study, they worked on primary teeth while the current study was conducted on permanent teeth. Similarly, Babu et al (4) concluded that green tea has a higher amount of remineralization ability as compared to black tea. They referred this result to the high catechin fraction which is responsible for its antibacterial properties.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations